Kontrol' sostojanija oporno-dvigatel'nogo apparata sportsmenov na nacal'nom i trenirovocnom etapach - Chesnokov, N. N.; Morozov, A. P.; Gayduk, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The result of management of the training process of young athletes is conditioned by both rational planning of the training process and the regular use of their health assessment in the process of sports training. At the same time, the attention of coaches and specialists in the training process is aimed at solving the problems of recruiting a sports form, including by increasing the volume and intensity of physical activity, starting from the stage of initial training. This leads to a deterioration in the condition of the articular-ligamentous apparatus, flattening of the arches of the foot, impaired posture and a number of other adverse consequences. Prevention and rehabilitation after the formation of sports training is often complicated by a period of intensive growth of the body in adolescence and the presence of chronic injuries. The use of modern technologies and means of diagnostics of the level of physical and technical readiness in children and youth sports, based on objective data, makes it possible to guarantee the timely detection of the slightest deviations, to record the dynamics of the growth of results and to ensure the development of effective training programs.